Hubungan Partisispasi, Sumber Daya, dan Motivasi dengan Efektivitas Program P2L Pada KWT Kecamatan Candi, Sidoarjo - Maharani, Sephia; Mubarokah; Risqi Firdaus Setiawan (Jurnal Agrosains dan Teknologi, 2025)
The Sustainable Food Home Garden Program (P2L) is a strategic initiative to optimize the utilization of home gardens as a source of family food and to improve food security through community empowerment. This research aims to analyze the relationship between member participation, resources, and member motivation with the effectiveness of the Sustainable Food Home Garden Program (P2L). The research was conducted using a quantitative descriptive method, with a saturated sample of 55 members from KWT Rukun Makmur and KWT Tani Segar. Data collection was carried out through questionnaires with a Likert scale and analyzed using descriptive statistics and Spearman's rank correlation. Results show that member participation has a moderately strong and significant positive relationship with program effectiveness (correlation coefficient 0.317, significance 0.018), while resources (correlation coefficient 0.220, significance 0.107) and member motivation (correlation coefficient 0.090, significance 0.512) only show very weak and non-significant positive relationships. The low correlation between motivation and program effectiveness is due to KWT members' motivation being mostly external, such as production facilities assistance, rather than internal drive to achieve family food self-sufficiency